Strategy of BAZNAS and Laku Pandai For Collecting and Distributing Zakah in Indonesia - Andiani, Kartika; Hafidhuddin, Didin; Beik, Irfan Syauqi; Ali, Khalifah Muhamad (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
As an important and potential instrument for national development, Zakah will continue to require development innovations. One of the innovation is through cooperation between BAZNAS and Laku Pandai which aims to achieve Zakah inclusion so that the collection and distribution of Zakah in Indonesia can increase. This cooperation is still relatively young so the implementation still needs to identify the problem and strategy. This study aims to analyze the strategic priorities for BAZNAS in running cooperation with Laku Pandai. This study used SWOT-ANP method with respondents as many as five expert respondents. The strategies derived from this research are the result of the formulation of a combination of SWOT factors. The main findings of this study indicate that the main priority of the overall strategy is strengthening the synergy of BAZNAS with the Laku Pandai of sharia banking. The results of this study can be a reference for BAZNAS and Laku Pandai in formulating implementation strategies for this cooperation.DOI: 10.15408/aiq.v10i2.6943